Multisite Electrophysiology Recordings in Mice to Study Cross‐Regional Communication During Anxiety. Issue 1 (13th February 2018) - Harris, Alexander Z.; Golder, Danielle; Likhtik, Ekaterina
Abstract: Recording neural activity in awake, freely moving mice is a powerful and flexible technique for dissecting the neural circuit mechanisms underlying pathological behavior. This unit describes protocols for designing a drive and recording single neurons and local field potentials during anxiety‐related paradigms. We also include protocols for integrating pharmacologic and optogenetic means for circuit manipulations, which, when combined with electrophysiological recordings, demonstrate input‐specific and cell‐specific contributions to circuit‐wide activity. We discuss the planning, execution, and troubleshooting of physiology experiments during anxiety‐like behavior. © 2017 by John Wiley & Sons, Inc.